2012
DOI: 10.3945/jn.112.158063
|View full text |Cite
|
Sign up to set email alerts
|

Children Live, Feel, and Respond to Experiences of Food Insecurity That Compromise Their Development and Weight Status in Peri-Urban Venezuela,

Abstract: Children's experiences of food insecurity (FI) may be conceptually distinct and different from those of adults. Previous study of children's experiences of FI has relied primarily on their parents' perspective. This study explored, described, and conceptualized experiences of FI in children attending 5 public schools in peri-urban areas of the Miranda State, Venezuela, South America using a naturalistic approach. Children aged 10-17 y were studied through focus groups (n = 42) and individual interviews (n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 26 publications
3
109
0
5
Order By: Relevance
“…Male respondents were more food secure (9, 2.9%) than females (7, 2.3%) though not significantly. Also recorded was that respondents in faculty of basic medicals were more food secure (6, 1.9%) while faculty of engineering shown the highest number of food insecure with severe hunger (36, 11.6%) followed by faculty of education (35,11.3%), though not significantly (table 3). Further analysis of food security revealed that respondents whose mother attained tertiary education were more food secure (11, 3.5%) than respondents whose mother's highest education attained was secondary level (5, 1.6); whereas respondents whose mother's educational qualification was primary, vocational/trained were not food secure and this is same for mothers with no formal education; but not significantly (table 4).…”
Section: B Food Security Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male respondents were more food secure (9, 2.9%) than females (7, 2.3%) though not significantly. Also recorded was that respondents in faculty of basic medicals were more food secure (6, 1.9%) while faculty of engineering shown the highest number of food insecure with severe hunger (36, 11.6%) followed by faculty of education (35,11.3%), though not significantly (table 3). Further analysis of food security revealed that respondents whose mother attained tertiary education were more food secure (11, 3.5%) than respondents whose mother's highest education attained was secondary level (5, 1.6); whereas respondents whose mother's educational qualification was primary, vocational/trained were not food secure and this is same for mothers with no formal education; but not significantly (table 4).…”
Section: B Food Security Of Respondentsmentioning
confidence: 99%
“…Effects of household food insecurity on children has been extensively researched [9], [10] evident in emotional disability and physical appearance [9], [10]- [11] Families with older children are reported to be more food insecure; compensatory feeding patterns engaged by low income families includes usage of nutrient supplement, high-energy boosters [12] and this is affect Globally there have been several moves by organizations to eradicate hunger and malnourishment. The first Millennium Development Goal (MDG) included in its targets the reduction by half of the amount of people who suffer from acute starvation and who earn less than $1 per day by the year 2015 [13].…”
Section: Introductionmentioning
confidence: 99%
“…To date there has been less extensive use of child self-report assessments of child food insecurity, but existing work supports the existence of common crosscultural domains. Studies in the United States and Venezuela both found that children experience awareness of food insecurity, including cognitive awareness, emotional or psychological awareness, and physical awareness [48,53]. There are also commonalities in how children take on responsibilities for managing food insecurity, including children's participation in parent-initiated strategies, and strategies that children initiate themselves.…”
Section: Common Domains Of Household Food Insecuritymentioning
confidence: 99%
“…Depending on the laws in each country, a procedure would be needed to establish responsibility for reporting and disclosure of child maltreatment, how to respond, and who should respond. The research done in the United States and Venezuela [48,53] on direct measurement with children has found that children as young as 7 years of age can respond accurately to questionnaire items, but further work should be done to determine the earliest age when child self-reporting is appropriate and who (e.g., caregiver, older sibling) should best be the reporter when children are too young to report for themselves. Other research in countries should be done to determine any differences by gender, what is the appropriate recall period, how do children understand time in relation to events, and what prompts can help children situate experiences accurately within time.…”
Section: Child-level Approachmentioning
confidence: 99%
See 1 more Smart Citation